2022
DOI: 10.1002/adfm.202112435
|View full text |Cite
|
Sign up to set email alerts
|

Selective Hydrogenation of Naphthalene to Decalin Over Surface‐Engineered α‐MoC Based on Synergy between Pd Doping and Mo Vacancy Generation

Abstract: Although the hydrogenation of aromatics is important for the processing of fossil fuels and biofuels, it typically requires costly (e.g., noble metal‐based) catalysts and exhibits unsatisfactory selectivity. Herein, flake‐like nanocrystalline molybdenum carbide (α‐MoC) is surface‐engineered via Pd doping, and the synergy between the in‐situ generated Mo vacancies and doped Pd species is shown to promote the selective hydrogenation of naphthalene to decalin. Experimental and theoretical evidence reveal that thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 69 publications
(83 reference statements)
1
11
0
Order By: Relevance
“…Our previous work demonstrated that a series of surface engineered structures in molybdenum carbide (a-MoC and b-Mo 2 C), including metal doping, vacancy generating, and metal supporting, could effectively modulate the surface chemical environment and electronic structure, thus leading to high catalytic performance. [35][36][37] In this work, we show the observation of lattice-contracted a-MoC induced by phase-transition engineering from a-MoC to b-Mo 2 C, as a result of enhanced HER catalytic activity. The optimized a-MoC-5 h (a-MoC pretreated in a CH 4 /H 2 atmosphere for 5 h) catalyst with 2.86% degree of lattice contraction exhibits greatly improved HER performance in both acid (h 10 ¼ 126 mV and h 50 ¼ 180 mV) and alkaline electrolytes (h 10 ¼ 122 mV and h 50 ¼ 156 mV), and outstanding stability over 120 hours.…”
Section: Introductionmentioning
confidence: 70%
“…Our previous work demonstrated that a series of surface engineered structures in molybdenum carbide (a-MoC and b-Mo 2 C), including metal doping, vacancy generating, and metal supporting, could effectively modulate the surface chemical environment and electronic structure, thus leading to high catalytic performance. [35][36][37] In this work, we show the observation of lattice-contracted a-MoC induced by phase-transition engineering from a-MoC to b-Mo 2 C, as a result of enhanced HER catalytic activity. The optimized a-MoC-5 h (a-MoC pretreated in a CH 4 /H 2 atmosphere for 5 h) catalyst with 2.86% degree of lattice contraction exhibits greatly improved HER performance in both acid (h 10 ¼ 126 mV and h 50 ¼ 180 mV) and alkaline electrolytes (h 10 ¼ 122 mV and h 50 ¼ 156 mV), and outstanding stability over 120 hours.…”
Section: Introductionmentioning
confidence: 70%
“…The demand for diesel worldwide in recent years has reached its highest level among petroleum products (27 million barrels per day in 2020), according to the World Energy Agency (IEA). Owing to the intensified scarcity of oil resources and deterioration of quality, the proportion of diesel from heavy oil fluid catalytic cracking (FCC) is increasing, which contains a great deal of polycyclic aromatic hydrocarbons (PAHs more than 70%). , However, these PAHs not only significantly reduce the cetane number of diesel but also wreak havoc on human health, environment, and engines’ life. As a result, many countries have enacted strict regulations to confine the PAH content in diesel (less than 7% in the Europe IV standard) …”
Section: Introductionmentioning
confidence: 99%
“…The hydrogenation of naphthalene is a reversible parallel–consecutive reaction giving tetralin and decalin (cis- and trans-isomers) . Notably, it is rather difficult to obtain pure decalin because of the stable aromatic ring in tetralin. , With the excellent solubility, volatility, and bicyclic alicyclic hydrocarbon structure, decalin is widely used as a raw material for drug intermediates, nylon production, and hydrogen storage. ,, In addition, trans-decalin possesses superior thermodynamic stability and optoelectronic property than cis-decalin, which makes the stereoselective hydrogenation of naphthalene to trans-decalin a promising process…”
Section: Introductionmentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbons (PAHs) make up an important pollutant that is harmful to the ecological environment, and they are also an important raw material for high value-added products. Naphthalene is the most abundant PAH in coal tar with a content of 8–12%, and naphthalene can be converted into tetralin and decalin through hydrogenation treatment. , Compared with naphthalene and decalin, tetralin has higher industrial value. As an ideal high boiling point solvent, tetralin is widely used in medicine, paint, papermaking, coatings, agrochemical, and other fields.…”
Section: Introductionmentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbons (PAHs) make up an important pollutant that is harmful to the ecological environment, 1 6 and they are also an important raw material for high value-added products. 7 9 Naphthalene is the most abundant PAH in coal tar with a content of 8–12%, and naphthalene can be converted into tetralin and decalin through hydrogenation treatment.…”
Section: Introductionmentioning
confidence: 99%